2021
DOI: 10.1080/02670836.2021.1996130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of constrained groove pressing on mechanical properties of a TWIP steel

Abstract: The evolution of mechanical properties and microstructure of a twinning induced plasticity (TWIP) steel sheet during constrained groove pressing (CGP) was investigated. It was found that by imposing CGP, the volume fraction of twins, hardness and yield strength increase significantly, while ductility decreases. The results of the pin-on-disk wear test showed that the CGP process improves the wear resistance of the TWIP steel, where oxidation is the main wear mechanism. The effect of annealing treatment at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Nazari et al 12 examined the effects of multi-cut contour method and friction coefficient on the residual stresses of CGPed worksheets. Shirani et al 13 investigated the influence of CGP on the twinning-induced plasticity of steel sheets. They observed that by conducting more CGP cycles, YS (yield strength), hardness, and volume fraction of twins increased sharply.…”
Section: Introductionmentioning
confidence: 99%
“…Nazari et al 12 examined the effects of multi-cut contour method and friction coefficient on the residual stresses of CGPed worksheets. Shirani et al 13 investigated the influence of CGP on the twinning-induced plasticity of steel sheets. They observed that by conducting more CGP cycles, YS (yield strength), hardness, and volume fraction of twins increased sharply.…”
Section: Introductionmentioning
confidence: 99%
“…Among various SPD methods accumulative roll-bonding (ARB) [5], and constrained groove pressing (CGP) [6,7] are suited for sheet materials. The CGP method has been employed to process different sheet metals including Al [8], copper [9][10][11], low carbon steel [3], Ni [12], NiTi [13], stainless steel [14], Ti [15], Ti6Al4V [16], and twinning induced plasticity high Mn steel [17].…”
Section: Introductionmentioning
confidence: 99%